Party Equipment Rental Application Using Website-Based Notification - M. Ari Adriansyah; Diana Diana; Anisya Sonita; Muntahanah Muntahanah (Jurnal Komputer, Informasi dan Teknologi, 2023)
This title of this reseach is Application of party Equipment Using Website-Based Notification. Karya Mandiri is one of the businesses engaged in services. Itoffers rental services for various kinds of products for weddings and other events. The problems that exist today are that the recording still uses a manual system, it has not taken advantage of technological sophistication by making consumers rent without having to come to the location.Basides recording the equipment availability is still not well organized. The research method applied was the System Development Life Cycle (SDLC) with the waterfall model method. Waterfall development itself has several stages in its development, including needs analysis, design, development, testing phase, and implementation in the real environment being expected to provide information about equipment rental to prospective tenants. Organized and clear applications are very important in the business world, especially in the rental business.